Intermittent peripheral tissue ischemia during coronary ischemia reduces myocardial infarction through a KATP-dependent mechanism: first demonstration of remote ischemic perconditioning. - Schmidt, MR; Smerup, M; Konstantinov, I; Shimizu, M; Li, J; Cheung, M; White, P; Kristiansen, S; Sorensen, K; Dzavik, V; Redington, A; Kharbanda, R (2007)
Remote ischemic preconditioning reduces myocardial infarction (MI) in animal models. We tested the hypothesis that the systemic protection thus induced is effective when ischemic preconditioning is administered during ischemia (PerC) and before reperfusion and examined the role of the K(+)-dependent ATP (K(ATP)) channel. Twenty 20-kg pigs were randomized (10 in each group) to 40 min of left anterior descending coronary artery occlusion with 120 min of reperfusion. PerC consisted of four 5-min cycles of lower limb ischemia by tourniquet during left anterior descending coronary artery occlusion. Left ventricular (LV) function was assessed by a conductance catheter and extent of infarction by tetrazolium staining. The extent of MI was significantly reduced by PerC (60.4 +/- 14.3 vs. 38.3 +/- 15.4%, P = 0.004) and associated with improved functional indexes. The increase in the time constant of diastolic relaxation was significantly attenuated by PerC compared with control in ischemia and reperfusion (P = 0.01 and 0.04, respectively). At 120 min of reperfusion, preload-recruitable stroke work declined 38 +/- 6% and 3 +/- 5% in control and PerC, respectively (P = 0.001). The force-frequency relation was significantly depressed at 120 min of reperfusion in both groups, but optimal heart rate was significantly lower in the control group (P = 0.04). There were fewer malignant arrhythmias with PerC during reperfusion (P = 0.02). These protective effects of PerC were abolished by glibenclamide. Intermittent limb ischemia during myocardial ischemia reduces MI, preserves global systolic and diastolic function, and protects against arrhythmia during the reperfusion phase through a K(ATP) channel-dependent mechanism. Understanding this process may have important therapeutic implications for a range of ischemia-reperfusion syndromes.